Q: 3x plus 2y equals 4 -3x plus 4y equals -10?

Write your answer...

(4, -1)

3x+2y-5=0 3x+2y=5 Im lost im only 12 work out the rest hope i helped

-3x + 2y = 9 2y = 3x + 9y = 1,5x + 4,5

3x + 2y = 7

3x-2y-7=0

3x + 2y = 8 This is an equation. It could be the equation of a line.

3x = 2y + 7 The standard form is: 3x - 2y - 7 = 0

3x+2y=6 2y=-3x+6 y=-1.5x+3

3x plus 2y can be expressed mathematically as (3x + 2y).

3x+2y=9 2y=9-3x y=-1.5x-4.5

3x+2y = 1 2y = -3x+1 y = -1.5x+0.5

3x + 2y = 12 ie 2y = 12 - 3x so y = 6 - 3x/2

Multiply the first equation by -3

The equation can be simplified to show a value of Y in terms of X. 3X + 2Y +2 = 4Y + 4 3X + 2 = 2Y + 4 3X -2 = 2Y and 2Y = 3X - 2 means that Y = (3/2 X) -1

-3x + 2y = 12-3x + 3x + 2y = 3x + 122y = 3x + 122y/2 = 3x/2 + 12/2y = (3/2)x + 6

3x + 5 + x + 10 + 2y 4x + 2y + 15 |:2 2x + y + 7.5 2x + y + 7.5 is equivalent to the original.

If: 3x+2y = 5x+2y = 7 Then: 3x+2y = 7 and 5x+2y = 7 Subtract the 1st equation from the 2nd equation: 2x = 0 or x = o By substitution: x = 0 and y = 3.5

3x = 2y + 3 3x -3 = 2y +3 -3 3x - 3 = 2y (3x -3)/2 = 2y / 2 y = 1/2 x (3x - 3) 3x = 2y +3 3x - 3x = -3x +2y +3 0 = -3x +2y +3 -1 x (0) = -1 x (-3x +2y +3) 0 = 3x - 2y -3

If: 3x+2y = 5x+2y = 14 Then: 3x+2y = 14 and 5x+2y =14 Subtract the 1st equation from the 2nd equation: 2x = 0 Therefore by substitution the solutions are: x = 0 and y = 7

If: 3x+2y = 5x+2y = 7 which is the same as 7 = 7 = 7 Then: 3x+2y = 7 and 5x+2y = 7 Subtracting equations: x = 0 Therefore by substitution: x = 0 and y = 3.5

3x - 2y = -10Subtract 3x from each side:-2y = -3x - 10Multiply each side by -1:2y = 3x + 10Divide each side by 2:y = 1.5x + 5

(1, 0)

(-1, 5)

(-1, 5)

3x = 2y + 3 3x -3 = 2y +3 -3 3x - 3 = 2y (3x -3)/2 = 2y / 2 y = 1/2 x (3x - 3) 3x = 2y +3 3x - 3x = -3x +2y +3 0 = -3x +2y +3 -1 x (0) = -1 x (-3x +2y +3) 0 = 3x - 2y -3